Juridical Analysis of The Rampant Practice of Dumping Based on Positive Law and Islamic Law - Al Rizal Gahwi; Mutimatun Niami (Proceeding International Conference Restructuring and Transforming Law, 2024)
Dumping is an act of price discrimination that includes the sale of goods abroad at a lower price than the same domestic goods or at a price different from the normal price with the aim of preventing a decrease in the price of goods purchased domestically, which can kill the goods market and result in company bankruptcy. This research uses a doctrinal (Normative) approach because this research focuses on laws that are considered norms or rules that apply in society and are used as a reference for everyone's behavior. In Law No. 10/1995 on Customs, as amended by Law No. 17/2006 on Customs, there are dumping provisions governing import and export in Indonesia. These provisions are listed in Chapter IV on anti-dumping duties and countervailing duties, where the first part regulates anti-dumping duties, namely from Article 18 to Article 20, and the second part regulates countervailing duties, namely from Article Human beings have the right to differ in value in Islamic law. However, if one spends money with the intention of harming others, it is haram according to the law: "There is no harm to oneself, and no harm to others." In other words, if one does so with the intention of harming others, it is haram.